Uji Banding Metode Isolasi DNA Sampel FTA Card menggunakan Kit Wizard® Genomic DNA Purification, PureLink® Genomic DNA, dan Chelex-100 - Dyah Aryani Perwitasari; Imaniar Noor Faridah; Yeni Alfiana Ratnasari; Kania Agustina; Ikrimah Nisa Utami; Rita Maliza (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
FTA Cards are an easy way to collect blood samples, deliveries, and stores. The totalvolume of blood samples is less is needed when compared to the blood samples taken through a vein(venipuncture). The purpose of this research is a method that can be applied to isolate DNA samplesfrom FTA Cards using the Wizard® Genomic DNA Purifi cation Kit (Promega), PureLink® GenomicDNA Kits, and Chelex-100. This research was a type of experimental research, and data analysis wasshowed in qualitative and quantitative descriptively. The samples used were 16 samples of human bloodtaken using a lancet and then placed on the FTA Card, sampling was done by accidental samplingtechnique. The variations of the PureLink® Genomic DNA kits method with the addition of SDS 10%showed thin and smear DNA bands on agarose gels. Furthermore, the Chelex-100 method showed aclear DNA band. The purity data obtained varied between 1 to 1.1 and concentrations between 190 to950 ng/μl. The conclusion of this study is DNA kits method with the addition of 10% SDS and theChelex-100 method still have impurities, with the purity value of DNA was less than 1.8 and a lowconcentration to be used as a DNA template for further molecular analysis.